Managing Chronic Respiratory Diseases: The Essential Contributions of Nursing, Pharmacy, Family Medicine, Medical Secretaries, and Radiology in Multidisciplinary Care - Soja Mazyed Nasar Alshammari,; Ahmed Alatwi,; Halimah Ali Musa,; Laila Ali Musa,; Halimah Zelai Obeid Saiegh,; Salman Saad Mohammad Shaber,; Naif Mutlaq Alkhammash,; Abdulelah Saleh Alodib,; Yazeed Mohammed Hizab Al Ghofaily,; Abdullah Dhafer Abdulrahman Alshehry,; Abrar Mohammed Alashbat,; Abrar Mohammed Alshakhs, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Chronic respiratory diseases (CRDs), including asthma, COPD, and bronchiectasis, are common ailments that impact the lives of millions of people globally. Such conditions are defined by chronic respiratory manifestations and impaired lung function, resulting in significant morbidity, reduced quality of life, and increased healthcare consumption costs. In this context, it can be stressed that the successful treatment of CRDs involves not only the medical aspects, but also the psychological and social factors. Integral to this process is the concept of interprofessional collaboration wherein healthcare professionals from the various disciplines work together in a coordinated fashion to address patient requirements. Aim of work: To explore the essential contributions of nursing, family medicine, medical secretaries, and radiology in managing chronic respiratory diseases within a multidisciplinary framework. Methods: We conducted a comprehensive search in the MEDLINE database's electronic literature using the following search terms: Managing, Chronic Respiratory Diseases, Contributions, Nursing, Pharmacy, Family Medicine, Medical Secretaries, Radiology, and Multidisciplinary Care. The search was restricted to publications from 2016 to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion: Chronic respiratory diseases continue to act as a major burden to patients and health care services across the globe. The treatment of these conditions involves interdisciplinary work closely involving nursing, pharmacy, and family medicine, medical secretaries, and radiology. All of the disciplines are instrumental in managing the needs of the CRD patient due to the various and sometimes even conflicting wants and needs as they go through a range of processes, including diagnosis, treatment, and instruction, as well as coordination of care services. Altogether, all of these specialists map the genuine and integrative patient-centered care model that actively contributes to positive changes in life quality and individual’s resilience when facing chronic diseases. The overall complexity of the healthcare delivery will keep changing, and consequently, the essential element of the multidisciplinary approach to CRD hence will guarantee patients the best care in more personalized care setting.